Numerical investigation on aerodynamic performance improvement of vertical-axis tidal turbine with super-hydrophobic surface. (1st December 2020) - Sun, Jinjing; Huang, Diangui
Abstract: Inspired by nature, more and more domestic and foreign scholars began to pay attention to the application of hydrophobic materials in various fields for military and civil applications. The suitable bionic super-hydrophobic surface (SHS) has high drag reduction effect because of the slip effect on the solid surface. This paper conducted numerical simulation to study the aerodynamic performance improvement of vertical-axis tidal turbine (VATT) with SHS on the airfoils. The influence of different inflow velocities, blade number and solidities of VATT with SHS are studied. The results show that the maximum energy efficiency can be increased by 16.5% at the inflow velocity U  = 3 m/s. The improvement of power coefficient is found greatly influenced by the inflow velocity, blade number and solidity at small tip-speed ratios, while the increment of the energy efficiency is almost independent to these aerodynamic parameters at high tip-speed ratios. Highlights: A vertical-axis tidal turbine with super-hydrophobic surface is proposed. Influences of inflow velocity, blade number and solidity on VATT with SHS are studied. The maximum power coefficient improved by SHS on hydro-airfoils can be 16.5% at U  = 3 m/s. The improvement of the power coefficient for two-blade VATT is larger than 7% for all TSRs investigated at U  = 1 m/s. Increment of energy efficiency at high TSRs is almost independent to aerodynamic parameters for blades number N  ≥ 3.